A long shadow - Todd, Charles (Todd, Charles. Inspector Ian Rutledge novels., 2006)
New Year's Eve, 1919. Called away from dinner at the home of friends, Scotland Yard Inspector Ian Rutledge finds a brass cartridge casing on the steps outside. While it looks identical to the countless others he'd seen during the war, this one has a mysterious engraving. Curious, he pockets it. But soon, he finds another-in a most unexpected place. The inspector knows the shells are for him-markers that point to unfinished business involving the terrible war he cannot leave behind. A survivor with a dark secret, Rutledge walks on the edge of sanity, filled with the abiding fear that someone will discover the guilt, the horror, the shock he carries deep within. And now someone is hunting him. But who? And will Rutledge live long enough to find out why?